Presencia de cadmio (Cd) en el cacao (Theobroma cacao L.) de exportación - Alvarez Velastegui, Julio Gabriel (2021)
Currently, according to soil quality criteria, Ministerial Agreement 097 - Annex 2 of the Environmental Quality Standard for soil resources and remediation criteria for contaminated soils, of the Ministry of the Environment of Ecuador, the normal value is 0.5 mg / kg of cadmium. Although cadmium in the soil is found in various natural forms, volcanic activity (including underground volcanism) is considered the largest natural source of cadmium release into the atmosphere. Among the main anthropogenic sources of cadmium in the soil, we can say that the direct application of phosphate fertilizers to soils occupies one of the first places. Phosphate fertilizers are one of the most ubiquitous sources of cadmium contamination in agricultural soils around the world, as cadmium often occurs in high concentrations in the phosphate rocks from which the fertilizer is produced. The bioavailability of cadmium to cocoa plants depends on several factors: CEC, pH, organic matter, soil texture, electrical conductivity, macro and micronutrients, influence of soil microorganisms on the behavior of cadmium in soils. In 2014, EU Regulation No. 488/2014 was issued, which establishes the maximum cadmium limits for chocolates and other derivatives. In accordance with the transition period of 5 years, compliance with it was required as of January 1, 2019. Several investigations carried out in our country have reported the presence of Cd at toxic levels in cocoa soils and cocoa beans with amounts greater than 1 mg / kg of Cd: in the provinces of El Oro, Guayas, Zamora, Los Ríos, Francisco de Orellana, Esmeraldas and the tropical part of Pichincha. So far, a value of 4,08 mg/kg of Cd has been found in almonds, which is the highest in the Province of El Oro; They are followed by Guayas and Manabí with 3,57 and 3,46 mg/kg, respectively. As for the province of Los Ríos, there is an average of 0,57 mg/kg, with a minimum of 0,23 mg/kg and a maximum of 1,23 mg/kg. The population intake of cadmium of products containing cocoa and derivatives ranges between 0,005 to 0,39 ug/kg of body weight per month, which is equivalent to 0,02 – 1,6 % tolerance, for people who mostly consume these products their This percentage will be considered from 30 to 69 % for adults and 96 % for children, not causing these reasons of concern to consumers.